Correlation of Androgen Deprivation Therapy with Cognitive Dysfunction in Patients with Prostate Cancer: A Nationwide Population-Based Study Using the National Health Insurance Service Database - Tae, Bum Sik; Jeon, Byung Jo; Shin, Seung Hun; Choi, Hoon; Bae, Jae Hyun; Park, Jae Young (Cancer research and treatment, 2019)
The purpose of this study was to evaluate the association of androgen deprivation therapy (ADT) with cognitive dysfunction. Using the National Health Insurance Service database of the entire Korean adult prostate cancer population (n=236,391), data on ADT and cognitive dysfunction between 2008 and 2015 were analyzed. We excluded patients previously diagnosed with cognitive dysfunction, dementia, or a cerebral event history. We tested the effect of ADT on the risk of cognitive dysfunction using propensity score-matched Cox proportional hazards regression models and Kaplan-Meier survival analysis. Our final cohort comprised of 35,401 individuals with prostate cancer, including 24,567 men (70.6%) who underwent ADT. During a mean follow-up period of 4.1 years, 4,741 patients were newly diagnosed with cognitive dysfunction. A statistically significant association was found between ADT and the risk of cognitive dysfunction (hazard ratio, 1.169; p=0.002). Meanwhile, age (≥ 70 years), diabetes, hypertension, cardiovascular history, and peripheral vascular disease were identified as factors that contribute to the increased risk of cognitive dysfunction. In contrast, the use of statins and aspirin was associated with a lower risk of cognitive dysfunction. Kaplan-Meier analysis demonstrated that patients aged 70 years or older who underwent ADT had the lowest cumulative probability of remaining cognitive dysfunction-free (log-rank p < 0.001). Our. revealed an association between the use of ADT for the treatment of prostate cancer and an increased risk of cognitive dysfunction in a nationwide population-based study. This finding should be further evaluated in prospective studies.